1943
DOI: 10.1037/h0059093
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of the Pacific edible crab, Cancer magister Dana.

Abstract: However, the behavior of Cancer magister has been mentioned only briefly (MacKay, 1931 and1942) and very little information is available in the literature concerning this economically important crustacean. It would therefore seem desirable to place on record the available information concerning the behavior of this crab.The observations reported herein were made chiefly at Crescent and at Prince Rupert, British Columbia during the period 1930-34 and 1941. Crescent is located on Boundary Bay, a large and relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
(1 reference statement)
1
10
0
Order By: Relevance
“…Dungeness crabs reach sexual maturity at a carapace width of 100 mm, which occurs at 2 years of age in Humboldt County, California; however, in Alaska, crab gonads are not fully developed at a carapace width of 100 mm, so eggs are not extruded until the following year ($3 years old) (Butler, 1961;Cleaver, 1949;Hankin et al, 1989;Scheding et al, 1999). When females are close to moulting, males become more active and move towards the nearshore (Barry, 1985;Cleaver, 1949;MacKay, 1942). Males will grasp and carry a female that is close to moulting for up to 2 weeks in a 'premating embrace'.…”
Section: Matingmentioning
confidence: 97%
See 1 more Smart Citation
“…Dungeness crabs reach sexual maturity at a carapace width of 100 mm, which occurs at 2 years of age in Humboldt County, California; however, in Alaska, crab gonads are not fully developed at a carapace width of 100 mm, so eggs are not extruded until the following year ($3 years old) (Butler, 1961;Cleaver, 1949;Hankin et al, 1989;Scheding et al, 1999). When females are close to moulting, males become more active and move towards the nearshore (Barry, 1985;Cleaver, 1949;MacKay, 1942). Males will grasp and carry a female that is close to moulting for up to 2 weeks in a 'premating embrace'.…”
Section: Matingmentioning
confidence: 97%
“…The larvae are often released as prezoea, and initially, researchers thought prezoea released into the water column did not survive, but more recent studies have demonstrated that prezoea survive and develop into stage-I zoea (Buchanan and Milleman, 1969;MacKay, 1942;Poole, 1966). In the laboratory, the transition from prezoea to stage-I zoea takes only a few seconds, and thus prezoea are only in the water column for seconds to minutes.…”
Section: Hatchingmentioning
confidence: 98%
“…positive phototaxis, negative geotaxis, positive barokinesis and/or thigmotaxis. These mechanisms are displayed by a variety of larvae (MacKay, 1943;Thorson, 1964;Rice, 1966;Sulkin, 1973;Ennis, 1975;Sulkin and Van Heukelem, in press), including the megalopae of Pachygrapsus crassipes (own obs.) and the post larvae of a galatheid crab which have been observed to be densely concentrated in banded slicks off New Zealand (Zeldis and Jillett, 1982).…”
mentioning
confidence: 99%
“…Juvenile crabs after settling are preyed upon by larger crabs (MacKay, 1942;Butler, 1954;Gotshall, 1977;Kurihara and Okamoto, 1987), and such cannibalism is an important factor in their mortality, along with larval mortality (Botsford and Wickham, 1978;Kurihara and Okamoto, 1987). On the other hand, it is recognized that some crabs are able to avoid extensive cannibalism (Stevens and Armstrong, 1984;Kurihara et al, 1988).…”
Section: Introductionmentioning
confidence: 98%
“…It is widely known that an intraspecific prey-predator relationship exists among crabs (MacKay, 1942;Butler, 1954;Fox, 1975;Gotshall, 1977;Botsford and Wickham, 1978;Polis, 1981;Stevens et al, 1982;Kurihara and Okamoto, 1987;Kurihara et al, 1988). Juvenile crabs after settling are preyed upon by larger crabs (MacKay, 1942;Butler, 1954;Gotshall, 1977;Kurihara and Okamoto, 1987), and such cannibalism is an important factor in their mortality, along with larval mortality (Botsford and Wickham, 1978;Kurihara and Okamoto, 1987).…”
Section: Introductionmentioning
confidence: 98%